Flambagem lateral com torção de vigas de aço em reigme elasto-plástico - Luiz Antonio de Souza (1999)
When a beam bent about its greatest axis moment of inertia, lateral deflection and twisting will occur when the applied load reaches its critical value, unless the beam is provided with properly spaced and designed lateral bracings or the cross section is torsionally stiff. For a perfectly straight beam, the critical load corresponds to the pointof bifurcation of equilibrium when out-of-plane bending and twisting deformations become the stable configuration of the member. The phenomenon is an ultimate limit state termed lateral-torsional buckling. The brazilian code NBR 8800/86, the american specification AISC/LRFD, the canadian specification CAN/CSA-S.16.1, and most of the specifications for the design of steel structures recommend the use of approximate expressions to obtain the value of the nominal strength of bending moment in the elastic and inelastic range. In these expressions beams with non-prismatic sections cannot be analyzed, the applied load and the presence of stabilizing and non-stabilizing load are not properly considered and the boundary conditions are limited to the case of constrained torsion and the translation in the buckling plane while the rotation and the warping are hold free. This study presents a numerical procedure, based on energy method, to obtain accurate results for the elastic and inelastic nominal strength to the lateral-torsional buckling, considering many different situations of loading, includingstabilizing and non-stabilizing actions, boundary conditions, including the case when the rotation in the buckling plane and the warping are constrained, and variation of the moment of inertia, with doubly-symmetric and singly-symmetric cross section, and with coped beams and beams with reinforcement or with web openings. Several cases are analyzed and the results are compared with those proposed by the design specifications for steel structures.